Strategi peningkatan kinerja Dinas Lingkungan Hidup dan Kehutanan dalam pencegahan kerusakan lingkungan hidup di Kabupaten Padang Lawas - Muhammad Saroha Lubis; Sofyan Husein Siregar; Samsir Samsir (Pelantar Press, 2019)
A performance enhancement strategy is a way that is done to better provide the potential in itself to achieve a goal. A performance enhancement strategy is an important thing to do as it can improve morals, loyalty, responsibility, discipline and, creativity and, well-being. The purpose of the author is to find out the perception of environment and forestry officers (DLHK) in the prevention of environmental damage and, to know DLHK's performance improvement strategy in the prevention of environmental damage in Padang Lawas district. Data used in this research is primary and secondary data, obtained through the data collection techniques triangulation are: observationand, interviewand questionnaire/poll. The Data obtained is analyzed using two analytical techniques namely qualitative descriptive analysis and SWOT analysis. After the analyst, it can be concluded that the perception of staff of Padang Lawas District in the prevention of environmental damage is carried out quite well. While the performance improvement strategies need to improve work and authority, improve the monitoring aspect, optimize budgets, make sanctions on employees who are less disciplined and, overcome cultural participation that is lacking in support and, promote a culture of caring environment to the entrepreneurs and society.